Pengaruh Geoboard Terhadap Hasil Belajar Matematika Siswa Pada Materi Segi Empat - Sri Agustin Limalo; Riyanti Ismail (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to determine the differences in mathematics learning outcomes of students who areusing taughtGeoboard and mathematics learning outcomes without using geoboard on rectangular flat material. The research method is an experiment conducted in class VII in the even semester of 2024/2025 academic year. The research design is counterbalanced design. The population in this study were all seventh grade students of SMP Negeri 1 Tilongkabila. The research sample was class VII-1 and VII-3, both were given the same treatment in a different order. Class VII-1 was initially taught using the guided discovery method with the help of a geoboard and class VII-3 was initially taught using the expository method. Then, the treatment was rotated after aheld post-test was . Sampling technique using Cluster Sampling. The research instrument is a multiple choice test of mathematics learning outcomes. Data analysis in hypothesis testing used the -t Polled Variance test with = 0.05 and dk = 39. This shows that tcount > ttabel. This means that the mathematics learning outcomes of students who are taught using the Guided Discovery method assisted by geoboardsrotation before and afterare higher than the Expository learning method. This means that the Guided Discovery method assisted by geoboards excels in teaching quadrilaterals in class VII SMP Negeri 1 Tilongkabila.